Analisis Tren Luas Wilayah dan Produksi Kelapa Sawit di Provinsi Aceh: Studi Kuantitatif dan Prediktif - Fadhilla, Cut Alna; Gunawan, Chichi Rizka; Sofia Amriza, Rona Nisa (Universitas Islam Negeri Sumatera Utara, 2025)
Palm oil is a strategic commodity that plays an important role in the economy of Aceh Province. This study aims to analyze the trend of changes in the area of oil palm plantations and their production results using quantitative data from recent years, as well as to predict palm oil production for the next five years. The methods used include descriptive statistical analysis to identify development patterns and predictive models based on time series forecasting to accurately estimate future trends. The results of the study show a significant increase in the area of land and oil palm production in several main districts, with Nagan Raya as the largest contributor. The prediction of harvest results for the next five years indicates a positive trend that can be used as a basis for planning the development of the plantation sector. These findings provide important information for policy makers and industry players in making strategic decisions to increase the productivity and sustainability of the oil palm business in Aceh Province. Keywords: Palm Oil Production, Area Analysis, Prediction Model